Preliminary investigation on architecture students’ perceptions of developing hard and soft skills via project-based learning - Wardah Fatimah Mohammad Yusoff; Nor Haslina Ja’afar; Noraziah Mohammad Zin (Penerbit Universiti Kebangsaan Malaysia, 2022)
In ensuring competitiveness and employability, architectural graduates nowadays have been observed to acquire new skills to complement their conventional architectural trainings. The main purpose of this paper is to discuss the hard and soft skills acquired by the architectural students via the architectural design project requirements, which is also categorized as project-based learning. The study utilizes mixed-mode methods through questionnaire survey and in-depth interview. As this is a preliminary study, the number of respondents for the survey is 32, while for the in-depth interview, only eight students have participated. From the findings, it can be concluded that skills such as video presentation (hard skill), teamwork and communication skills (soft skill) are essential for architecture students undertaking project-based learning. The findings of this study will be used to benefit investigations in student’s skill developments in project-based learning with larger number of respondents. It is hoped that the findings will be adopted into the architectural education field to better equip future graduate architects with skills which are necessary for the industry.